2019
DOI: 10.1021/acsomega.9b01659
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Non-Surface-Active Langmuir Trough Subphases from Milk

Abstract: Milk polar lipid interfacial behavior continues to be analyzed using Langmuir trough experiments, but the reported Langmuir trough subphases commonly used are not fully representative of milk. A method to transform liquids of biological origin, such as milk, into appropriate Langmuir trough subphases does not currently exist, which hinders the applicability of Langmuir trough experiments to nature. Here, a procedure to manufacture milk-derived Langmuir trough subphases with insignificant amounts of surfactants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Surface active solution is defined as the solution whose surface tension decreases upon compression. Real Hernandez & Jimenez-Flores (2019), found that the permeate of skim milk was also surface-active, may be due to trace proteins and peptides present in the concentrated protein. It was found that ultrafiltration and solvent induced emulsions can be used to make milk into a Langmuir trough subphase, and the surfactants can be removed from milk without adding foreign substances.…”
Section: Milk Concentrationmentioning
confidence: 99%
“…Surface active solution is defined as the solution whose surface tension decreases upon compression. Real Hernandez & Jimenez-Flores (2019), found that the permeate of skim milk was also surface-active, may be due to trace proteins and peptides present in the concentrated protein. It was found that ultrafiltration and solvent induced emulsions can be used to make milk into a Langmuir trough subphase, and the surfactants can be removed from milk without adding foreign substances.…”
Section: Milk Concentrationmentioning
confidence: 99%